2016
DOI: 10.1053/j.ajkd.2016.02.044
|View full text |Cite
|
Sign up to set email alerts
|

Pre-existing and Postoperative Intimal Hyperplasia and Arteriovenous Fistula Outcomes

Abstract: Background The contribution of intimal hyperplasia (IH) to arteriovenous fistula (AVF) failure is uncertain. This observational study assessed the relationship between preexisting, postoperative, and change in IH over time and AVF outcomes. Study Design Prospective cohort study with longitudinal assessment of IH at the time of AVF creation (pre-existing) and transposition (postoperative). Patients were followed-up for up to 3.3 years. Setting & Participants 96 patients from a single center who underwent AV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
79
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(87 citation statements)
references
References 21 publications
6
79
2
Order By: Relevance
“…These studies emphasized the profound histologic differences between preexisting and postoperative IH ( Figure 1). Postoperative lesions are recognized as eccentric concentrations of myofibroblasts in the intima of AVFs and AVGs (9,10,15), whereas the preexisting venous pathology consists of concentric accumulations of both myofibroblasts and contractile VSMCs underneath the endothelial line (10,13). The National Institute of Diabetes and Digestive and Kidney Diseases-funded multicenter, observational Hemodialysis Fistula Maturation (HFM) Study confirmed the high prevalence of preexisting IH in veins used to create an AVF in 370 patients with CKD.…”
Section: Ih Pathobiology Of Preexisting Ihmentioning
confidence: 91%
See 3 more Smart Citations
“…These studies emphasized the profound histologic differences between preexisting and postoperative IH ( Figure 1). Postoperative lesions are recognized as eccentric concentrations of myofibroblasts in the intima of AVFs and AVGs (9,10,15), whereas the preexisting venous pathology consists of concentric accumulations of both myofibroblasts and contractile VSMCs underneath the endothelial line (10,13). The National Institute of Diabetes and Digestive and Kidney Diseases-funded multicenter, observational Hemodialysis Fistula Maturation (HFM) Study confirmed the high prevalence of preexisting IH in veins used to create an AVF in 370 patients with CKD.…”
Section: Ih Pathobiology Of Preexisting Ihmentioning
confidence: 91%
“…Although it is unlikely that postoperative IH alone leads to critical AVF occlusion (10), it may be a contributing factor to AVF nonmaturation in the setting of inadequate outward remodeling. More recently, IH has been also identified as a common preexisting (13,14).…”
Section: Ih Pathobiology Of Preexisting Ihmentioning
confidence: 99%
See 2 more Smart Citations
“…Of note, the contribution of each of these factors to AVF failure is not certain and further research is warranted to determine the role of upstream and downstream events on stenosis. While IH is historically associated with stenosis and early failure of vascular accesses based on histologic observations, a recent study showed that it is improbable that this lesion alone causes critical AVF stenosis (12). This may explain why drug eluting stents or local delivery of anti-proliferative agents have shown promising results in animal models (13), but have failed to improve human AVF maturation outcome (14, 15)…”
Section: Introductionmentioning
confidence: 99%